Asymptotic Series of General Symbol of Pseudo-Differential Operator Involving Fractional Fourier Transform. (24th September 2013) - Upadhyay, S. K.; Kumar, Anuj; Dubey, Jitendra Kumar
Abstract : An asymptotic series of general symbol of pseudo-differential operator is obtained by using the theory of fractional Fourier transform.